Implementasi Strategi Alih Wahana Cerpen ke Dalam Bentuk Puisi Pada Siswa Kelas XI - Randy, Dinda Aulia; Septiana, Ika; Asrofah, Asrofah; Warkito, Petrus Joko (Innovative: Journal Of Social Science Research, 2024)
This research aims to examine the implementation of the strategy of converting short stories into poetry in class XI students at SMK Negeri 6 Semarang. Translation is the process of transposing a literary work from one form to another, with the aim of maintaining the essence and main message of the original work. In an educational context, this strategy is used to increase students' appreciation and understanding of literary works. The research method used is classroom action research (PTK) with a qualitative approach. The research subjects were class XI students at SMK Negeri 6 Semarang. Data was collected through observation, interviews and document analysis. The results of the research show that the implementation of the short story translation strategy into poetry is able to increase students' creativity and analytical skills towards literary works. Students become better able to identify themes, messages and characters in short stories, and express them again in the form of poetry. Apart from that, this strategy also provides a more interesting and interactive learning experience for students, thereby increasing their motivation in studying literature. It is hoped that these findings can make a positive contribution to the development of literature teaching methods in vocational schools.